2021
DOI: 10.1080/1331677x.2021.1874460
|View full text |Cite
|
Sign up to set email alerts
|

Do clustered firms outperform the non-clustered? Evidence of financial performance in traditional industries

Abstract: Previous research presented in numbers of studies strongly suggests that locating in a cluster generates valuable benefits to clustered firms. These include better access to suppliers and other scarce inputs, superior knowledge and innovation, a better position from which to build a social network as well as proximate to successful competitors. Yet when the positive impact of agglomeration and clustering has been questioned on the strictly financial performance of clustered firms, the results of these studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
(93 reference statements)
1
13
0
1
Order By: Relevance
“…Inter-organizational collaboration within a cluster allows achieving a synergy effect through the sharing of resources, use of common infrastructure, and coordination of strategies (Sheresheva 2010;Khakimov 2019;Razminien ė et al 2021). One can say that the competitiveness of clusters lies within the most common things: knowledge, relationships, innovations, a common pool of resources, and digital transformations (Pavelkova et al 2021). At the same time, if we consider clusters as network structures (Bergenholtz and Waldstrøm 2011), then there is a need for a mechanism to align the different interests of stakeholders and coordinate their actions.…”
Section: Industrial Cluster As An Inter-organizational Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-organizational collaboration within a cluster allows achieving a synergy effect through the sharing of resources, use of common infrastructure, and coordination of strategies (Sheresheva 2010;Khakimov 2019;Razminien ė et al 2021). One can say that the competitiveness of clusters lies within the most common things: knowledge, relationships, innovations, a common pool of resources, and digital transformations (Pavelkova et al 2021). At the same time, if we consider clusters as network structures (Bergenholtz and Waldstrøm 2011), then there is a need for a mechanism to align the different interests of stakeholders and coordinate their actions.…”
Section: Industrial Cluster As An Inter-organizational Networkmentioning
confidence: 99%
“…Actually, benefits for cluster members are usually asymmetric (McCann and Folta 2011). Some authors also argue that in many cases, clustering appears to be not a way to develop competitiveness but simply a way to survive (Pavelkova et al 2021).…”
Section: Industrial Cluster As An Inter-organizational Networkmentioning
confidence: 99%
“…It is often suggested that companies that belong to a cluster often outperform companies that work on their own. Advantages such as higher salaries, better recognition of a product or service provided, easier access to funding, frequent participation in fairs, as well as better financial indicators and many more are mentioned in scientific literature [19]. Clusters can be initiated through different perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the role and position of universities in industrial clusters has received attention. Many authors [5,7] believe that universities "open the door" to the world of international cooperation and partners and provides an irreplaceable research base. Also under discussion are the conditions for the creation of associations, such as first-rate, efficient organizational structures, coordination and information networks, stimulation of interaction, and issues of size and distribution of resources [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors [5,7] believe that universities "open the door" to the world of international cooperation and partners and provides an irreplaceable research base. Also under discussion are the conditions for the creation of associations, such as first-rate, efficient organizational structures, coordination and information networks, stimulation of interaction, and issues of size and distribution of resources [7]. Some analyses of the conceptual gaps in cluster theory point to the inefficiency of large corporations' participation in clusters and argue that it is only beneficial to small businesses with the help of large partners [7].…”
Section: Introductionmentioning
confidence: 99%